Adansonia digitata L. – A review of traditional uses, phytochemistry and pharmacology - De Caluwé, Emmy; Halamová, Kateřina; Van Damme, Patrick (Afrika Focus, 2010)
Baobab (Adansonia digitata L., Malvaceae) is a multi-purpose tree species native to Africa. Its fruit pulp has very high vitamin C content (ffi ten times that of orange), and can be used in seasoning, as an appetizer and to make juices. Seeds contain appreciable quantities of crude protein, digestible carbohydrates and oil, whereas they have high levels of lysine, thiamine, Ca and Fe. They can be eaten fresh or dried, ground into flour and thus added to soups and stews. Processing eliminates a number of anti-nutritional factors present in the seed. Baobab leaves are superior in nutritional quality to fruit pulp, and contain significant levels of vitamin A. The leaves are a staple for many populations in Africa, and are eaten fresh or dried. Several plant parts have interesting anti-oxidant and anti-inflammatory properties, and baobab has been used extensively since ancient times in traditional medicine. Key words: Baobab, Adansonia digitata L., traditional use, phytochemistry, pharmacology, amino acids, fatty acids, minerals, vitamins, anti-nutritional factors